The Effect of Concentration Areca Seed Extract (Areca Catechu L.) on Physicochemical and Sensory Properties of Pineapple Juice (Ananas Comosus L. Merr) As a Functional Beverages - Purba, Daniel Tua; Nizori, Addion; Wulansari, Dian (Department of Technology of Agricultural product (THP) Jambi University, 2022)
This study aims to determine the effect of concentration areca seed extract on the physicochemical and sensory properties of pineapple juice as a functional beverages , and to determine the appropriate concentration of areca seed extract to produce pineapple juice that has the best physicochemical and sensory properties. This study used a completely randomized design (CRD) consisting of 4 levels of treatment, namely the concentration of areca seed extract 0%, 1%, 2%, and 3% (v/v). Each treatment was repeated 5 times, so there were 20 experimental units. The results showed that the concentration of areca seed extract had a significant effect on the total soluble solids, the degree of warmth L* and a*, antioxidant activity, total tannin, vitamin C levels, and had no significant effect on the acidity (pH), and had a characteristic taste of pineapple chelate until the taste of pineapple is slightly chelate, the color is brown to very brown, it has a pineapple aroma to a strong pineapple aroma, with a weak aftertaste to a slightly strong after taste. The best treatment in making pineapple juice with areca seed extract was the concentration of 2% areca seed extract which contained 80.02% antioxidant activity, vitamin C 104.68 mg/100 g, total tannin 99.62 mg TAE/g, total dissolved solids value 20.980brix, color degree value L*29.48, a*7.06, b*20.80, acidity value (pH) 3.37, has a slightly brown color, aroma of pineapple (methyl ester and ethyl ester compounds), taste pineapple and not chelate, and has no aftertaste.